Miniopen vs Lateral Approach for Ankle Arthrodesis, Which Approach is Superior in Joint Preparation: A Cadaver Study. Issue 4 (16th October 2019) - Chinnakkannu, Karthikeyan; McKissack, Haley; Viner, Gean C.; He, Jun Kit; Moraes, Leonardo V. M.; Montgomery, Tyler; Wilson, John T.; Anderson, Matthew; Buddemeyer, Katherine
Category: Ankle, Ankle Arthritis, Arthroscopy, Basic Sciences/Biologics Introduction/Purpose: Ankle arthrodesis is a gold standard for end-stage ankle arthritis after conservative managements fail. It may be done through direct anterior, lateral, arthroscopic or mini open approaches. Joint preparation, apposition of joint surfaces and stable fixation are very important for successful outcomes. Ankle arthrodesis maybe associated with infection, chronic pain and nonunion - of these, nonunion is the most common complication reported. Achieving union is of utmost importance while minimizing complications associated with the procedure. Regardless of approach or fixation method, preparation of articular surface is of paramount importance for successful union and may be limited by the approach used. Our study aims to evaluate the difference between direct lateral and dual mini-open approaches (extended arthroscopic portals) in terms of joint preparation. Methods: We used 10 below knee fresh-frozen cadaver legs for this cadaveric study. Ankle joints of five specimens were prepared through the lateral approach, while the remaining five ankles were prepared using dual mini incisions. After the completion of preparation, all ankles were dissected to open, photographic images of tibial plafond and talar articular were taken. Surface areas of each articular facet and unprepared cartilage of the talus, distal tibia, and distal fibula were measured and analyzed using ImageJ software. Results: Significantly greater amount of total surface area was prepared among specimens using mini-open approach compared to those with trans-fibular approach. The percentage of total articulating surface area prepared (including talus and tibia/fibula), talus, tibia and fibula in trans-fibular approach were 76.9%, 77.7% and 75% respectively. The percentages were 90.9%, 92.9%, and 88.6% in mini-open approach. While the medial gutter was well prepared with mini incision technique (unprepared surface 44 .64% vs 91.08%), lateral gutter was well prepared in trans-fibular technique (88.82vs 82.04 square cm). There is no difference in the amount of unprepared surface of talar dome between the two approaches. When excluding the medial gutter, there was no significant difference between trans-fibular and mini open techniques (83.94 vs 90.85, p=0.1412). Conclusion: Joint preparation using the mini-open approach (extended arthroscopic portal) is equally as efficacious as the transfibular approach for preparation of the tibiotalar joint. When including preparation of the medial gutter, the mini-open approach provides superior joint preparation. This may be advantageous with decreased rate of nonunion and less complications. But many surgeons fuse only tibiotalar surface, considering that, both approaches yield equal amount of joint preparation. But it needs to be confirmed with clinical studies.